Use of recombinant bovine cytokines in pigs vaccinated and challenged with Streptococcus suis - Frank Blecha; D N Reddy; C G Chitko-McKown; M M Chengappa; D S McVey; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1991)
An experiment was conducted to determine the adjuvanticity of recombinant bovine interleukin-1β (rBoIL-1β) and recombinant bovine interleukin-2 (rBoIL-2) administered in conjunction with a single S. suis vaccination in pigs. Sixty, 4-wk-old pigs were allotted to 8 groups: 1) nonvaccinated controls; 2) vaccinated controls; 3) rBoIL-Iβ, 100 ng/kg; 4)rBoIL-lβ, 1000 ng/kg; 5) rBoIL-1β, 10,000 ng/kg; 6) rBoIL-2, 2.5 µg/kg; 7) rBoIL-2, 25 µg/kg; and 8) rBoIL-2, 250 µg/kg. All pigs (except group 1) were vaccinated on d 0 with a commercial S. suis vaccine (serotypes 1 and 2). At vaccination, pigs were injected intramuscularly with their respective cytokine treatments. Pigs received additional cytokine injections for 2 consecutive days. On d 21, all pigs were injected intravenously with 3.5 x 109 CFU of a log phase culture of S. suis (serotype 2). The highest dose of rBolL-1β exceeded the maximum tolerable dose for the cytokine; however, this dose of rBoIL-1β protected pigs from the S. suis challenge. In pigs receiving rBoIL-1β at 10,000 ng/kg, pathological lesions caused by S. suis were lowest when compared to other treatment groups. No mortality from S. suis challenge was observed in pigs that received the highest dose of rBoIL-1β. These data clearly show that rBoIL-1β (10,000 ng/kg), administered intramuscularly for 3 consecutive days at vaccination, is more effective than the S. suis vaccine alone in protecting pigs against a S. suis challenge.; Swine Day, Manhattan, KS, November 21, 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Cytokine; Adjuvant; Pig; Vaccine